Características das lesões desportivas e fatores associados com lesão em iniciantes de ginástica artística do sexo feminino - Vanderlei, Franciele Marques; Vanderlei, Luiz Carlos Marques [UNESP]; Netto Júnior, Jayme [UNESP]; Pastre, Carlos Marcelo [UNESP] (Universidade de São Paulo (USP), 2013)
The artistic gymnastics is a modality that associates arts with biomechanical gestures, and it has been prominent among children and adolescents. Its practice can lead to sports injuries; therefore, it is important to know the factors inherent to trauma for the formulation of preventive models. Thus, the objective of this study was to characterize sports injuries and to verify factors associated with injury in people practicing artistic gymnastics with different levels of competitiveness. Forty-six gymnasts were interviewed with mean age of 10.1±2.0 years for female participants, who were classified in two competitive levels, i.e, initiation and training. We used the morbidity questionnaire adapted to sports characteristics to collect personal, training, and injury data. It was observed that injury risk was 0.3 injuries per athlete and 1.4 injuries per injured athlete, in which the gymnasts of the training category showed a higher frequency of the injury (83.3%; n=10) compared with the ones in the initiation category (10.5%; n=4). For both levels of competitiveness, training moment and light severity were the most reported variables. In the mechanism, contactless was more prevalent in the training category (90%; n=9) and the direct contact was more common at initiation category (75%; n=3). Anthropometric and training variables were considered as factors associated with injury to the gymnasts. It is concluded that gymnasts of the training category have higher injury frequency. Anthropometric and training variables were factors associated with injury. Characteristics of the injuries depend on the competitiveness level of the gymnasts.

A ginástica artística é uma modalidade que combina arte a gestos biomecânicos e tem se destacado entre crianças e adolescentes. Sua prática pode conduzir a lesões desportivas, por isso é importante conhecer os fatores inerentes ao traumatismo para formulação de modelos preventivos. Desse modo, objetivou-se caracterizar as lesões desportivas e verificar os fatores associados com lesão em praticantes de ginástica artística de diferentes níveis de competitividade. Foram entrevistadas 46 ginastas, com média de idade de 10,1±2,0 anos do sexo feminino, classificadas em dois níveis competitivos: iniciação e treinamento. Utilizou-se o inquérito de morbidade referida adaptado com as características da modalidade para reunir dados pessoais, de treinamento e da lesão. Foram observadas 0,3 lesões por atleta e 1,4 lesões por atleta lesionado, em que ginastas da categoria de treinamento apresentaram maior frequência de lesão (83,3%; n=10) do que as de iniciação (10,5%; n=4). Para ambos os níveis, o momento treinamento e a gravidade leve foram os mais relatados. No mecanismo, o sem contato foi mais prevalente na categoria de treinamento (90%; n=9) e o contato direto foi o mais frequente na iniciação (75%; n=3). As variáveis antropométricas e de treinamento foram consideradas fatores associados com lesão para as ginastas. Conclui-se que ginastas da categoria de treinamento possuem maior frequência de lesão. As variáveis antropométricas e de treinamento foram fatores associados com lesão. As características das lesões dependem do nível de competitividade das ginastas.

La gimnasia artística es una modalidad que combina arte y gestos biomecánicos, y es destacada entre niños y adolescentes. Su práctica puede conducir a lesiones deportivas, por eso es importante conocer los factores inherentes al traumatismo para la formulación de modelos preventivos. De ese modo, el objetivo de este estudio es caracterizar las lesiones deportivas y verificar los factores asociados con lesión en practicantes de gimnasia artística de diferentes niveles de competitividad. Fueron entrevistadas 46 gimnastas, con edad media de 10,1±2,0 años de sexo femenino, clasificadas en dos niveles competitivos: iniciación y entrenamiento. Se utilizó la encuesta de morbilidad adaptada a las características de este deporte para recabar datos personales, de entrenamiento y de lesión. Fueron observadas 0,3 lesiones por atleta y 1,4 lesiones por atleta lesionado, en que gimnastas de la categoría de entrenamiento presentaron mayor frecuencia de lesión (83,3%; n=10) comparadas con las de iniciación (10,5%, n=4). Para ambos niveles, el momento de entrenamiento y la gravedad leve fueron los más relatados. En cuanto al mecanismo, el sin contacto fue el más prevalente en la categoría de entrenamiento (90%; n=9) y de contacto directo fue el más frecuente en la iniciación (75%; n=3). Las variables antropométricas y de entrenamiento fueron consideradas factores asociados con lesión para las gimnastas. Se concluye que las gimnastas de la categoría de entrenamiento poseen mayor frecuencia de lesión. Las variables antropométricas y de entrenamiento fueron factores asociados con lesión. Las características de las lesiones dependen del nivel de competitividad de las gimnastas.
Características de las lesiones deportivas y factores asociados con lesión en iniciantes de gimnasia artística del sexo femenino
Characteristics of sports injuries and factors associated with injury in beginners of female artistic gymnastics
Keywords: traumatismos em atletas; inquéritos de morbidade; epidemiologia; estudos transversais; prevalência; athletic injuries; morbidity surveys; epidemiology; cross-sectional studies; prevalence